Game on: do children absorb sports sponsorship messages? - Pettigrew, Simone; Rosenberg, M.; Ferguson, R.; Houghton, S.; Wood, L. (Cambridge University Press, 2013)
OBJECTIVE: It is likely that there are substantial subconscious effects of organizations’ efforts to associate their products with sport via sponsorships, but most research methods are unable to capture these effects. The present study employed a novel projective technique to explore children's implicit associations between popular sports and a range of sports sponsors.DESIGN: Children participated in an activity using magnets bearing the logos of numerous sports and sponsors. They were invited to arrange the magnets on a whiteboard without being advised that the activity related to sponsorship.SETTING: Perth, Western Australia.SUBJECTS: Children (n 164) aged 5–12 years.RESULTS: Three-quarters (76 %) of the children aligned at least one correct sponsor magnet with the relevant sport. Just over half the children (54 %) correctly matched the most popular sport (an Australian Football League team) with its relevant sponsor (a fast-food chain).CONCLUSIONS: Given the unstructured nature of the projective task, the results provide some support for the argument that sports sponsorship can effectively reach child audiences. This is of concern given the current extent of sponsorship by alcohol and fast-food companies.